The tyrosine kinase inhibitor toceranib in feline injection site sarcoma: efficacy and side effects. (14th January 2016) - Holtermann, N.; Kiupel, M.; Hirschberger, J.
Abstract: Because of their locally invasive growth and high recurrence rate despite of aggressive local therapy, treatment of feline sarcomas is challenging. The tyrosine kinase inhibitor (TKI) toceranib is currently licensed for the treatment of canine mast cell tumours. There are only few reports about TKI usage in cats. Previous studies indicated promising potential of TKI for the treatment of feline injection site sarcoma (FISS). In this prospective clinical trial, 18 cats with unresectable FISS were treated at a target dosage of 3.25 mg kg −1 every other day to evaluate the clinical efficacy and toxicity of toceranib. There was no clinical response measurable. Adverse events were generally mild and temporary. Grade 3 or 4 adverse events developed infrequently and all resolved with drug holidays and dose reductions.